2014
DOI: 10.1371/journal.ppat.1004005
|View full text |Cite
|
Sign up to set email alerts
|

A Highly Conserved Toxo1 Haplotype Directs Resistance to Toxoplasmosis and Its Associated Caspase-1 Dependent Killing of Parasite and Host Macrophage

Abstract: Natural immunity or resistance to pathogens most often relies on the genetic make-up of the host. In a LEW rat model of refractoriness to toxoplasmosis, we previously identified on chromosome 10 the Toxo1 locus that directs toxoplasmosis outcome and controls parasite spreading by a macrophage-dependent mechanism. Now, we narrowed down Toxo1 to a 891 kb interval containing 29 genes syntenic to human 17p13 region. Strikingly, Toxo1 is included in a haplotype block strictly conserved among all refractory rat stra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
70
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(74 citation statements)
references
References 35 publications
(59 reference statements)
3
70
0
Order By: Relevance
“…In the case of intracellular T. gondii, lysosomal fusion of the nonfusogenic parasitophorous vacuole leads to killing of the intracellular parasites (34). Consistent with our observation that scavenging ROS augments parasite survival and growth in the LEW rat peritoneal cells, others (11) have demonstrated the involvement of ROS and caspase-1 in a T. gondii killing mechanism that is linked to the Toxo1 locus in the LEW rat.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In the case of intracellular T. gondii, lysosomal fusion of the nonfusogenic parasitophorous vacuole leads to killing of the intracellular parasites (34). Consistent with our observation that scavenging ROS augments parasite survival and growth in the LEW rat peritoneal cells, others (11) have demonstrated the involvement of ROS and caspase-1 in a T. gondii killing mechanism that is linked to the Toxo1 locus in the LEW rat.…”
Section: Discussionsupporting
confidence: 90%
“…The resistance phenotype of the LEW rat peritoneal macrophages to T. gondii infection has been associated with the rapid death of both parasites and infected host cells (10,11). Thus, we endeavored to investigate whether the increase in T. gondii growth in LEW rat peritoneal cells treated with MnTBAP would lead to a higher cell death rate in the LEW than in the BN rat peritoneal cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, a recent study showed that T. gondii induced the NOX1-dependent production of excessive ROS, which contributed to mitochondrial structural damage and mitochondrial dysfunction in placentas, as well as the cleavage of caspase-9 and caspase-3, which resulted in the apoptosis of trophoblasts (35). T. gondii also induced pyroptosis-like features with ROS production, as well as the activation of caspase-1 and IL-1␤ secretion, in macrophages (36). Our results correlate with those of previous studies that showed that NOX is an important source of GRA7-induced ROS that initiate intracellular signaling cascades.…”
Section: Discussionmentioning
confidence: 99%
“…Toxoplasma gondii infection has been shown to induce inflammasome activation that is dependent on NLRP1B in mice and on NLRP1A in rats (15)(16)(17)23). There are two NLRP1 paralogs in rats (Nlrp1a and Nlrp1b) (24): the Nlrp1a paralog is associated with rat macrophage susceptibility to LeTx (25), but little is known about the Nlrp1b paralog.…”
Section: Discussionmentioning
confidence: 99%